Pengaruh Pengalaman Kerja, Independensi, Obyektifitas, Integritas, dan Kompetensi terhadap Kualitas Audit pada BPKP Kantor Perwakilan Wilayah Jawa Timur - Dhea Arie Thalia; Sumadi (Jurnal Akuntansi Terapan dan Bisnis, 2021)
This study aims to examine the effect of work experience, independence, objectivity, integrity, and competence on the quality of audits produced by public sector auditors at BPKP East Java Regional Representative Office. This study uses quantitative methods with research instruments using questionnaires. The population of this study are public sector auditors who become Civil Servants (PNS) at BPKP East Java Regional Representative Office. Determination of the sample with the criteria that the auditor has attended the Auditor Functional Position Education and Training (JFA). Analysis of research data using multiple linear regression. The results showed that the independence, integrity, competence of public sector auditors had no effect on audit quality. While the variables of Work Experience, Objectivity affect the quality of audits produced by public sector auditors at BPKP East Java Regional Representative Office.